2014
DOI: 10.3389/fgene.2014.00422
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs regulate NF-κB signaling to modulate blood vessel inflammation

Abstract: Cardiovascular diseases such as atherosclerosis are one of the leading causes of morbidity and mortality worldwide. The clinical manifestations of atherosclerosis, which include heart attack and stroke, occur several decades after initiation of the disease and become more severe with age. Inflammation of blood vessels plays a prominent role in atherogenesis. Activation of the endothelium by inflammatory mediators leads to the recruitment of circulating inflammatory cells, which drives atherosclerotic plaque fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 184 publications
(246 reference statements)
2
61
0
Order By: Relevance
“…In this study, genetic disruption of miR-155 was associated with increased circulating levels of proinflammatory cytokines and increased parasitemia during PbA infection. Conflicting roles for miR-155 in inflammation have been described (50). miR-155 has been shown to target suppressor of cytokine signaling 1, thereby modulating IFN-γ signaling, but this miRNA has also been proposed to genes at distal sites (39,40).…”
Section: Mir-155mentioning
confidence: 99%
“…In this study, genetic disruption of miR-155 was associated with increased circulating levels of proinflammatory cytokines and increased parasitemia during PbA infection. Conflicting roles for miR-155 in inflammation have been described (50). miR-155 has been shown to target suppressor of cytokine signaling 1, thereby modulating IFN-γ signaling, but this miRNA has also been proposed to genes at distal sites (39,40).…”
Section: Mir-155mentioning
confidence: 99%
“…Cardiovascular diseases are among them. Because there are already thorough reviews that summarize current knowledge about miRs implicated in atherosclerosis susceptibility, development, and progression [81][82][83][84][85][86][87][88] , we will focus on the part of atherosclerosis pathology where different miRs could potentially alter vascular physiology by the direct or indirect regulation of CXCL16 gene expression.…”
Section: Rs3744700 (T/g)mentioning
confidence: 99%
“…Mice deficient in miR-146a have prolonged T-cell responses, excessive and lethal responses to endotoxin and develop autoimmunity and tumors. 18 These phenotypes are invariably associated with enhanced and prolonged NF-κB-dependent responses.…”
mentioning
confidence: 99%
“…In the case of miR-146a, multiple components of proinflammatory signaling pathways (including TRAF6, IRAK1, IRAK2, MyD88, RelB, STAT1, CARD10, and TLR4) have been identified as bona fide targets. 18 Deletion of miR-146a in mice has revealed that this microRNA dampens and extinguishes inflammatory signaling cascades. Mice deficient in miR-146a have prolonged T-cell responses, excessive and lethal responses to endotoxin and develop autoimmunity and tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation